Migration and Development in Manjushree Thapa’s Seasons of Flight: A Global Perspective - Adhikari, Rishiram (Nepal Journal of Multidisciplinary Research, 2022)
The paper analyzes the Manjushree Thapa's Seasons of Flight from the perspective migration and development. Prema the main characters of the novel migrates from Nepal to USA through EDV and see dream of better future, however, she cannot be satisfied with economic prosperity. In this context the study focuses on how Prema is being victim of globalization and migrations and what are problems she faced in her life. Qualitative research design was followed and analyzed the issue with textual evidence. Conclusion has been made on the basis of textual analysis. Through analysis it is proved that Prema wants to be a rich and prestigious personality but she could not be happy in life because she could not feel enjoy in her life.